Synthesis and thermal characterization of phosphorus- containing siliconized epoxy resins - Kumar, S. Ananda (2006)
Siliconized epoxy matrix resin was developed by reacting diglycidyl ethers of bisphenol A (DGEBA) type epoxy resin with hydroxyl terminated polydimethylsiloxane (silicone) modiWer, using -aminopropyltriethoxysilane crosslinker and dibutyltindilaurate catalyst. The siliconized epoxy resin was cured with 4, 4-diaminodiphenylmethane (DDM), 1,6-hexanediamine (HDA), and bis (4-aminophenyl) phenylphosphate (BAPP). The BAPP cured epoxy and siliconized epoxy resins exhibit better Xame-retardant behaviour than DDM and HDA cured resins. The thermal stability and Xame-retardant property of the cured epoxy resins were studied by thermal gravimetric analysis (TGA) and limiting oxygen index (LOI). The glass transition temperatures (Tg) were measured by diVerential scanning calorimetry (DSC) and the surface morphology was studied by scanning electron microscopy (SEM). The heat deXection temperature (HDT) and moisture absorption studies were carried out as per standard testing procedure. The thermal stability and Xame-retardant properties of the cured epoxy resins were improved by the incorporation of both silicone and phosphorus moieties. The synergistic eVect of silicone and phosphorus enhanced the limiting oxygen index values, which was observed for siliconized epoxy resins cured with phosphorus containing diamine compound.